Development of Evaluation Tools Based on Kahoot! Application on the Material of Diversity of Indonesian Society in Class VII of SMPN 2 Timpah Petak Puti, Timpah District - Kristanto, Andi; Karliani, Eli; Saefulloh, Ahmad (JURNAL PENDIDIKAN, 2024)
This study aimed to develop a learning media evaluation tool on the material of Indonesian Community Diversity in Class VII of SMP N 2 Timpah Petak Puti, Timpah District. The advantages and disadvantages of finding out the Development of an Application-Based Evaluation Tool Kahoot! on the Material of Indonesian Community Diversity in Class VII of SMP N 2 Timpah Petak Puti, Timpah District. This type of research is development research or Research and Development (R&D). The researcher used the Borg and Gall development model in this development research. To produce a learning media evaluation tool based on Kahoot! which has gone through the validation, trial, and revision stages. This research was conducted at SMPN 2 Timpah Petak Puti. The results of this learning evaluation tool were declared valid and suitable for use based on the assessment of material experts, namely Pancasila and Citizenship Education subject teachers and student questionnaires consisting of 3 aspects, namely: learning media aspects, material aspects, and benefits aspects. The assessment of material experts obtained a score of 30 in the "Good" category, while the student rate through the questionnaires obtained a score of 198 in the "Very Good" category.